The Effect of the Teams Challenge Strategy on Acquisition and Developing Critical Thinking Among Second Intermediate Grade Students in History - Qadir, Asst.L. Omar Mustafa Abdul Qadir Abdul (Sulaimani Journal for Humanities, 2026)
This research aims at identifying the effect of the Teams Challenge Strategy on acquisition and developing critical thinking among second intermediate grade students in the subject of history. To achieve the objectives of the research, the researcher followed the procedures of the experimental method. The researcher randomly selected Al-Asma’i Secondary School for Boys, in which the second intermediate grade consists of two sections. The researcher randomly chose Section (A) to represent the experimental group, which was taught according to the Teams Challenge strategy, and their number was (25), and Section (B) to represent the control group, which was taught using the traditional method, and their number was (23). The researcher prepared two tests: · The first was to measure the acquisition of historical concepts. · The second was a test to measure thinking. Data were processed using: (t-test for independent samples, t-test for paired samples, and Pearson correlation coefficient). After statistically analyzing the results, the researcher concluded that there are statistically significant differences between the mean scores of the students in the two research groups in the tests of acquiring historical concepts and critical thinking, in favor of the experimental group. Some recommendations and suggestions were presented.
Keywords: Strategy; Teams Challenge; Acquisition; Development; Critical Thinking